2008
DOI: 10.1007/bf02982158
|View full text |Cite
|
Sign up to set email alerts
|

Unintended weight loss in the elderly living at home: The aged in home care project (ADHOC)

Abstract: Abstract:Objective: To describe associations between unintended weight loss (UWL) and characteristics of nutritional status. Design: A comparative cross-sectional assessment study at 11 sites in Europe. The target population was a stratified random sample of 4,455 recipients of home care (405 in each random sample from 11 urban areas) aged 65 years and older. Measurements: the Resident Assessment Instrument for Home Care, version 2.0. Epidemiological and medical characteristics of clients and service utilisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
3
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 30 publications
(23 reference statements)
3
46
3
5
Order By: Relevance
“…Social factors A large cohort study (n = 4010) found that reduced social activity is an independent contributor to unexplained weight loss in the older person (OR 2.0, 95% CI 1.6-2.5). 7 Additionally, a retrospective chart review of 96 residents in six intermediate care facilities in the United States showed that unexplained weight loss was most prevalent among the lowest income group. 8 In summary, determination of potential contributing factors to weight loss should not focus solely on disease-related processes.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Social factors A large cohort study (n = 4010) found that reduced social activity is an independent contributor to unexplained weight loss in the older person (OR 2.0, 95% CI 1.6-2.5). 7 Additionally, a retrospective chart review of 96 residents in six intermediate care facilities in the United States showed that unexplained weight loss was most prevalent among the lowest income group. 8 In summary, determination of potential contributing factors to weight loss should not focus solely on disease-related processes.…”
Section: Psychological Factorsmentioning
confidence: 99%
“…Eleven percent and 10% of the CSGs, respectively, reported dementia/cognitive decline and poor oral health (difficulty chewing or poor dentition) as recommended language for the etiology component of the term. Older adults with cognitive impairment have increased risk of unintended weight loss (54) and adverse outcomes (19,(54)(55)(56). Poor oral health is a contributing factor in the development of involuntary weight loss in the frail elderly population wearing ill-fitting dentures or edentulous (53) and leads to use of texture-modified diets, a validated etiology for involuntary weight loss by the CSGs.…”
Section: Missing Languagementioning
confidence: 99%
“…Weight loss could accelerate sarcopenia in elder adults [19]. The significant association between unintentional weight loss and reduction in ADL and IADL functions could also be found [20]. For older women experienced weight loss, they had higher rates of hip-bone loss and a two-fold greater risk of subsequent hip fracture [21] and the risk of frailty fracture had also been increased substantially [22].…”
Section: Introductionmentioning
confidence: 94%